Extrinsic rewards and job satisfaction among employees in RISDA Selangor / Nur Masriyah Hamzah and Syafawati Matkhairuddin - Hamzah, Nur Masriyah; Matkhairuddin, Syafawati (2022)
From the perspective of human resource management, the reward system is measured as one of the most important elements and is motivated by extrinsic rewards or financial rewards that can lead to a positive impact on employee job satisfaction. Therefore, this study aims to investigate the relationship between extrinsic rewards and job satisfaction and examine the extrinsic factors that affect employees' job satisfaction. The extrinsic or financial rewards such as base salary raise, salary increment, and promotion have been discussed in this study. Employees working at the Rubber Industry Smallholders Development Authority office located in Shah Alam, Selangor were taken as samples for this study. 40 questionnaires were distributed and 36 were collected for analysis. Statistical Package for Social Science version 28 was employed to perform the descriptive analysis while Spearman correlation analysis was done to establish the relationship between independent and dependent variables. The results revealed that there was a strong positive monotonic correlation between extrinsic rewards and job satisfaction, which was highly statistically significant (rs(34)=.977, p=.001). Thus, hypothesis 1 was supported. This implies that extrinsic rewards raise the level of employees' job satisfaction and can, ultimately increase the organisation's productivity. Therefore, the results of this study can be a useful guideline for RISDA organisation to improve its reward system and hopefully be able to satisfy employees' needs and simultaneously achieve higher employee satisfaction.